The Role of Social Media as a Guide and Reference During Travel: Case Study on Indonesian Millennial Tourists in Japan - Septia Winduwati; Cahaya Rizka Putri (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
Social media plays a central role in travel planning, particularly among Indonesian millennial tourists who seek information, inspiration, and real-time guidance. This study examines how social media shapes the behavior of Indonesian tourists visiting Japan, employing the framework of digital tourism communication and the theory of electronic word-of-mouth (eWOM). A mixed-methods design was applied, combining a survey of 494 respondents with in-depth interviews to explore travel habits, digital engagement, and decision-making processes. Findings reveal that Instagram and TikTok serve as primary triggers of travel inspiration, while YouTube, blogs, and Google Reviews are primarily used for information verification and detailed itinerary planning. User-generated content (UGC) is perceived as more credible than commercial content, underscoring the importance of authenticity and trust. However, the viral nature of social media also contributes to overtourism, highlighting the need for sustainable destination management strategies. Theoretically, this study advances the literature by linking UGC, flow experience, and travel decision-making in the context of a developing country. Practically, it provides recommendations for destination managers, policymakers, and service providers to leverage social media strategically while promoting responsible and sustainable tourism practices.